2005
DOI: 10.1101/gr.4212705
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic structure of the SPANX gene cluster mapped to the prostate cancer susceptibility locus HPCX at Xq27

Abstract: Genetic linkage studies indicate that germline variations in a gene or genes on chromosome Xq27-28 are implicated in prostate carcinogenesis. The linkage peak of prostate cancer overlies a region of ∼750 kb containing five SPANX genes (SPANX-A1, -A2, -B, -C, and -D) encoding sperm proteins associated with the nucleus; their expression was also detected in a variety of cancers. SPANX genes are >95% identical and reside within large segmental duplications (SDs) with a high level of similarity, which confounds mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 54 publications
4
59
0
Order By: Relevance
“…25,34 So far, the function of SPANXB or the other SPANX genes has not been studied in detail, but all five SPANX genes are present on the 750 kb Xq region linked to prostate cancer susceptibility, and deregulation of either one has been suggested as a possible mechanism for malignant transformation of prostate cells. 35 This is supported by experimental models showing that ectopic expression of SPANXC induces transformation in mammalian cells. 35 The association between SPANXB expression and presence of ETV6/RUNX1 may also be of importance for future treatment modalities, as SPANXB, normally present only in the immune-privileged testis, has been suggested to be an ideal target for tumor immunotherapy.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…25,34 So far, the function of SPANXB or the other SPANX genes has not been studied in detail, but all five SPANX genes are present on the 750 kb Xq region linked to prostate cancer susceptibility, and deregulation of either one has been suggested as a possible mechanism for malignant transformation of prostate cells. 35 This is supported by experimental models showing that ectopic expression of SPANXC induces transformation in mammalian cells. 35 The association between SPANXB expression and presence of ETV6/RUNX1 may also be of importance for future treatment modalities, as SPANXB, normally present only in the immune-privileged testis, has been suggested to be an ideal target for tumor immunotherapy.…”
Section: Discussionsupporting
confidence: 59%
“…35 This is supported by experimental models showing that ectopic expression of SPANXC induces transformation in mammalian cells. 35 The association between SPANXB expression and presence of ETV6/RUNX1 may also be of importance for future treatment modalities, as SPANXB, normally present only in the immune-privileged testis, has been suggested to be an ideal target for tumor immunotherapy. 34 18 smoothed z-scores (25-probe sliding mean) were plotted for all cases.…”
Section: Discussionsupporting
confidence: 59%
“…Originally, the SPANX family of genes was proposed as putative candidates for the HPCX-susceptibility locus. 43 However, recent studies have not identified mutations in any of these genes that definitely account for PrCa risk in X-linked HPC families. 44 Also found by conditioning on linkage to chromosome 2 was a significant peak on 12q21-q23, with an OSA LOD of 3.67 in families unlinked to chromosome 2.…”
Section: Discussionmentioning
confidence: 99%
“…These data were confirmed by an increased expression of the protein LDOC-1 in the tissues of PCa patients compared with normal prostate tissues. Gene conversions on the X chromosome (LDOC-1 maps in Xq27) have been linked with genetic diseases and disorders (21). These variations lead to haplotypes with an increased susceptibility to PCa; therefore it cannot be excluded that any rearrangements may favor an overexpression of LDOC-1 in PCa.…”
Section: Discussionmentioning
confidence: 99%